The Use of Technology in The Approximation of Didactic Units in The Training of Future Mathematics Shooters on The Basis of Innovative Education - Nafasov Ganisher Abdurashidovich; Davlatov Utkir Tagayevich; Komilov Mirziyo Mirkomilovich (Genius Journals, 2023)
In this article, the question of the application of the technology of didactic unit approximation of future mathematics shooters in the conditions of innovative education today is justified, or rather, the fact that it can be used in the training of basic concepts of umatematic analysis on the basis of contextual education, on the example of the first excellent limit.
Keywords: Enlargement of the didactic units; contextual learning; mathematical analysis